2000
DOI: 10.1093/rheumatology/39.4.407
|View full text |Cite
|
Sign up to set email alerts
|

A 1-year follow-up study of dynamic magnetic resonance imaging in early rheumatoid arthritis reveals synovitis to be increased in shared epitope-positive patients and predictive of erosions at 1 year

Abstract: These results show that dynamic MRI can be used to score synovitis objectively in early RA patients. Synovitis was greater in SE+ patients, suggesting an early genetic influence on joint inflammation, and was predictive for the development of erosions at 1 yr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 18 publications
3
67
0
5
Order By: Relevance
“…Kraan et al's investigation showed that leflunomide effectively reduced macrophage migration and numbers of adhesion molecules and also suppressed inflammatory cytokines more than antiinflammatory cytokines. The early reduction of synovial inflammation, as shown by the reduced IRE and numbers of immunologic markers (20), may offer a physiologic explanation for the early improvement in RA signs and symptoms with leflunomide treatment observed in clinical trials (26).…”
Section: Discussionmentioning
confidence: 97%
“…Kraan et al's investigation showed that leflunomide effectively reduced macrophage migration and numbers of adhesion molecules and also suppressed inflammatory cytokines more than antiinflammatory cytokines. The early reduction of synovial inflammation, as shown by the reduced IRE and numbers of immunologic markers (20), may offer a physiologic explanation for the early improvement in RA signs and symptoms with leflunomide treatment observed in clinical trials (26).…”
Section: Discussionmentioning
confidence: 97%
“…Details of the dynamic MRI scans performed at baseline in this cohort have been described previously (10). Briefly, dynamic scans used a coronal fatsuppressed fast multiplanar spoiled GRASS technique.…”
Section: Methodsmentioning
confidence: 99%
“…We and other investigators have studied MRI as a potential tool for prognostication in RA (8)(9)(10)(11)(12)(13). For the past 6 years, we prospectively studied a cohort of patients with early RA, monitoring their clinical and radiographic progression as well as the MRI appearance of their dominant wrists.…”
mentioning
confidence: 99%
“…Previous longitudinal studies of the wrist and/or finger joints have suggested an association between the synovial volume/enhancement rate (dynamic MRI) at baseline and the rate of erosive progression [13,14,15,16]; however, the predictive values of bone oedema, number of joints with enhancement and effusion in the wrist, metacarpophalangeal (MCP), proximal interphalangeal (PIP) and distal interphalangeal (DIP) joints still remain to be clarified. If specific MRI features can be used for prognostication, drug regimens may be adjusted according to disease severity for individual patients.…”
mentioning
confidence: 99%